Abstract Some Teaching Quality Criteria In Mentally Disabled Children's Learning and Its Acceptance By Their Teachers - Nsaif, Adel (Journal of Physical Education, 2016)
The importance of the research lies paying attention to mentally disabled children and special learning styles to teach them. The aim of the research is to identify the rate of teachers' acceptance of teaching quality criteria in mentally disabled Educational institutes. The problem of the research lies in the lack of criteria in these institutes. The researcher hypothesized the teachers' acceptance of quality teaching criteria. The research finally concluded that criteria standards are accepted and recommended the necessity of working with such criteria in mentally disabled institutes.